2020
DOI: 10.1002/celc.202000782
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Assisted Growth of CsPbBr3‐Based Solar Cells Without Selective Contacts

Abstract: In this work we report a simple and cost-effective CsPbBr 3based solar cell without ordinary selective contacts. To do so we follow an electrochemical approach consisting of three successive steps: (1) electrodeposition of PbO 2 directly on top of FTO substrates, (2) heterogeneous phase reaction with gaseous HBr and (3) spin-coating of methanolic CsBr solutions followed by annealing. This method is more adequate for largescale environmentally friendly production as it reduces chemical waste, particularly toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…This value is in the same order of that calculated from the solar simulator (AM 1.5 spectrum) used in the photoelectrochemical measurements (4.5×10 16 photons s −1 cm −2 ). Here, only photons with sufficient energy to create mobile electron‐hole pairs were considered, that is those with energy higher than that corresponding to the previously determined bandgap (511 nm) [33] . On the other hand, very recently Herz and colleagues have proven the short lifetimes of photogenerated carriers (∼ns) and the prevalence of monomolecular recombination for polycrystalline CsPbBr 3 films grown on quartz at illumination fluences several orders of magnitude higher than those calculated in our experiments [99] .…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…This value is in the same order of that calculated from the solar simulator (AM 1.5 spectrum) used in the photoelectrochemical measurements (4.5×10 16 photons s −1 cm −2 ). Here, only photons with sufficient energy to create mobile electron‐hole pairs were considered, that is those with energy higher than that corresponding to the previously determined bandgap (511 nm) [33] . On the other hand, very recently Herz and colleagues have proven the short lifetimes of photogenerated carriers (∼ns) and the prevalence of monomolecular recombination for polycrystalline CsPbBr 3 films grown on quartz at illumination fluences several orders of magnitude higher than those calculated in our experiments [99] .…”
Section: Resultsmentioning
confidence: 67%
“…Recombination studies also revealed the prevalence of Schockley-Read-Hall mechanism in this FTO/MAPI interphase as in the case of our recently reported FTO/CsPbBr 3 /C solar cell. [33,100] Regarding the aforementioned analysis, if it is assumed that CsPbBr 3 films grown either on quartz or FTO have similar short carrier lifetimes at room temperature, this feature would not contribute to compensate the usual poor charge collection in FTO/perovskite interphases. [100,102] In fact, carrier lifetimes in the order of microseconds would be necessary to suppress recombination in such interphase thus improving charge collection in FTO.…”
Section: Chemphyschemmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the ED of TMOs, one of the perovskites presents the (important) difference that the different steps are conducted in different processes and environments and not at the same time. For the electrochemical preparation of perovskites, two different pathways can be outlined (Figure 4): it is possible to deposit lead oxide PbO 2 (Figure 4a) [68,69] or PbO [70] similarly to what discussed in the case of transition metal oxides. The PbO 2 film requires a Pb 4þ reduction step, which can be carried out with H 2 [71] or halohydric acids.…”
Section: Electrodeposited Perovskitesmentioning
confidence: 99%
“…The PbO 2 film requires a Pb 4þ reduction step, which can be carried out with H 2 [71] or halohydric acids. [68,72] The PbO film is converted to PbI 2 by acid leaching in hydroiodic acid (HI) solution and then submerged to a methylammonium iodide (MAI) solution to obtain the perovskite in the final state of utilization. Alternatively, the conversion steps from lead oxides to lead halide perovskites can be conducted in the gas phase, [72] as demonstrated on textured Si.…”
Section: Electrodeposited Perovskitesmentioning
confidence: 99%